Using grounded nonlinear energy sinks to suppress lateral vibration in rotor systems. (1st June 2019) - Yao, Hongliang; Cao, Yanbo; Ding, Zhiyu; Wen, Bangchun
Highlights: A piecewise stiffness grounded nonlinear energy sink for rotor system was proposed. The GNES can suppress transient shock vibration in rotor systems. The wide-band vibration suppression ability of the GNES was verified. The GNES was proved to have better vibration suppression ability than absorber. Abstract: Modern rotating machineries require vibration suppression devices with simple structure and wide band effective vibration suppression frequency range, so a grounded nonlinear energy sink (GNES) with piecewise linear stiffness is developed to satisfy the requirements. Firstly, the structure and working principles of the GNES is explained. Then, the piecewise linear stiffness characteristic of elastic rods is analyzed and the dynamic equations for the rotor-GNES system are established, in which the rotor system is assumed to be either isotropic or anisotropic; numerical simulations are then carried out to study the vibration suppression effect of the GNES, and the wide-band vibration suppression capability of the GNES is assessed; comparison is made between the vibration suppression effect of the GNES and that of the dynamic vibration absorbers. Finally, experiments are carried out on a rotor-GNES system test platform to verify the suppression effects. The results show that the GNES is effective at suppressing vibrations in terms of both transient and steady-state vibrations within a rotor system. In the numerical simulation an optimal vibration suppression rate of 78% is achieved and in the test a rate of 68% is achieved.